2010
DOI: 10.3892/or_00000903
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin induces G2/M cell cycle arrest and apoptosis through MAPK and p53 signaling pathways in HepG2 cells

Abstract: Abstract. Oridonin, the main active constituent of Isodon rubescen, has antihepatocarcinoma activity in experimental and clinical settings. The aims of the study were to explore the anticancer effect of oridonin in HepG2 cells and to investigate the underlying mechanisms. Results showed that oridonin treatment for 24 or 48 h resulted in a marked decrease in cell viability time-and dose-dependently. IC 50 values were determined as 38.86 μM and 24.90 μM for 24-h and 48-h treatments, respectively. Flow cytometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Investigations reported that ORI induces phase G2/M cell cycle arrest and apoptosis in human hepatoma (HepG2) cells through the alteration of MAPK and p53 metabolic pathways (Wang et al, 2010). Another study indicated that upregulation of Glycyl-tRNA synthetase and heterochromatin protein 1 beta might facilitate inhibitory effects of ORI on tyrosine kinase and telomerase, respectively, in HepG2 cells (Wang, Ye, Pan, et al, 2011).…”
Section: Liver Cancermentioning
confidence: 99%
“…Investigations reported that ORI induces phase G2/M cell cycle arrest and apoptosis in human hepatoma (HepG2) cells through the alteration of MAPK and p53 metabolic pathways (Wang et al, 2010). Another study indicated that upregulation of Glycyl-tRNA synthetase and heterochromatin protein 1 beta might facilitate inhibitory effects of ORI on tyrosine kinase and telomerase, respectively, in HepG2 cells (Wang, Ye, Pan, et al, 2011).…”
Section: Liver Cancermentioning
confidence: 99%
“…Administration with germacrone could increase the production of ROS, following by promoted cleavage of caspase 3 and gasdermin E, thereby promoting pyroptosis of HepG2 cells. Furanodiene ( 24 ) is another active sesquiterpenoid from Ezhu and could induce HepG2 cell arrest at G2/M and apoptosis ( 47 ). The apoptosis induction effect of furanodiene was achieved by activating mitochondrial signaling pathway, including promoting mitochondrial transmembrane depolarization, release of mitochondrial cytochrome c and cleavage of PARP, and activating caspases−3.…”
Section: Anti-hcc Mechanism Of Active Sesquiterpenoidsmentioning
confidence: 99%